Penguatan Kualitas Produk, Pengelolaan, dan Pemasaran Sirup Sapodilla 'Putri' - Siti Shoimah; Afril Efan Pajri; Fatichatur Rochmaniyah; Eka Fadlilatus Saadah; Muhammad Sholihin (Amalee: Indonesian Journal of Community Research and Engagement, 2025)
This community service program was carried out to empower the Home Industry (IRT) of “Putri” Sapodilla Syrup in Pangkatrejo Village, Sugio Subdistrict, Lamongan. The partner faced challenges in three main aspects: inconsistent product quality and a short shelf life due to limited production technology, weak business management systems and financial record-keeping, and a marketing strategy limited to conventional promotional methods. The implementation method consisted of five stages: socialization, training, application of appropriate technology, mentoring, and evaluation. Interventions included the use of pasteurization machines, heavy-duty blenders, pH meters, refractometers, and vacuum sealers to improve product hygiene and shelf life. In terms of management, training was provided on digital financial recording, brand identity development, and simple business archiving. In marketing, redesigned packaging was introduced through Canva Pro, the activation of social media accounts (Instagram and TikTok), and distribution via e-commerce platforms (Shopee). The results showed significant improvements: the syrup product can now last up to three months without preservatives, sales increased by up to 30% within six months, and the partner’s managerial skills improved through digital record-keeping. Specifically, the partner’s average monthly revenue increased from IDR 3,000,000 before the program to approximately IDR 4,000,000 - 4,200,000 after the interventions. This program contributes to the achievement of SDGs 8, 9, and 12, and supports the strengthening of a green economy based on local potential.